Piramidy egipskie – groby faraonów czy spichlerze Józefa - Kaczmarek, Hieronim (Folia Praehistorica Posnaniensia, 2018)
This article is an attempt to take a new look at the research on the Egyptian pyramids conducted until the end of the nineteenth century in Poland.